1196. A Multi-faceted, Iterative Program to Increase COVID-19 Vaccine Uptake in a Midwestern HIV Clinic. (4th December 2021) - Bares, Sara H; Carr, Rachelle; Jones, Samantha L; Regan, Nichole N; Orduna, Valentina; Cramer, Daniel W; Tran, Christine D; Fadul, Nada
Abstract: Background: The National Institutes of Health Office of AIDS Research recommend that patients with HIV be prioritized for COVID-19 vaccination due to high rates of co-morbidities and sociodemographic risk factors that place them at increased risk for severe disease. However, COVID-19 vaccines were not distributed specifically to those in high-risk medical categories in Nebraska, and HIV clinics were not included in the state's COVID-19 vaccine delivery system. As a result, barriers to vaccine uptake emerged and interventions to mitigate them were needed. Methods: A multi-faceted and iterative program aimed at improving COVID-19 vaccine uptake was implemented at the University of Nebraska Medical Center's (UNMC) HIV clinic in Omaha, Nebraska in January 2021. A multidisciplinary task force was established in late January 2021 and met on a weekly basis to provide staff and patient education, linkage to vaccines, and review and analysis of vaccine completion rates as shown in the figure. Outreach interventions were continuously revised based on patient and staff feedback as well as updated data and vaccine availability. Multidisciplinary COVID-19 Task Force Overview Overview of the outreach interventions and activities conducted by the COVID-19 task force Results: All 1188 patients of the UNMC HIV clinic were ultimately eligible for the COVID-19 vaccine, but availability was on a rolling basis by age group, profession, county, and, ultimately, co-morbidities. 76% were male, 45.8% non-white, median age 48, and 73% had income less than 400% of federal poverty level. Of the 1188 eligible patients, 63.1% (n=751) had received at least one dose the COVID-19 vaccine and 59.3% (n=705) had completed the COVID-19 vaccine series by June 4, 2021. In comparison, 49.32% of the population of the state of Nebraska had initiated the COVID-19 vaccine series and 43.12% had completed the vaccine series by that date. Among our clinic patients, 27.9% (n=261) of those who had received at least one vaccine were assisted by our task force. 4.5% were noted to have a potential barrier at the time of outreach and these included hesitancy (3.5%), language (1.2%) and transportation (0.9%). Conclusion: A multi-faceted and iterative program to improve COVID-19 vaccine uptake in a high-risk patient population resulted in high rates of vaccine completion. Disclosures: Sara H. Bares, MD, Gilead Sciences (Grant/Research Support)Janssen (Grant/Research Support)ViiV Healthcare (Grant/Research Support)